2021
DOI: 10.3390/cells10020371
|View full text |Cite
|
Sign up to set email alerts
|

PBK/TOPK: A Therapeutic Target Worthy of Attention

Abstract: Accumulating evidence supports the role of PDZ-binding kinase (PBK)/T-lymphokine-activated killer-cell-originated protein kinase (TOPK) in mitosis and cell-cycle progression of mitotically active cells, especially proliferative malignant cells. PBK/TOPK was confirmed to be associated with the development, progression, and metastasis of malignancies. Therefore, it is a potential therapeutic target in cancer therapy. Many studies have been conducted to explore the clinical applicability of potent PBK/TOPK inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 73 publications
0
43
0
Order By: Relevance
“…Although previous studies [1,26,27] have reported higher expression of the PBK/TOPK mRNA and protein in tumor tissues than in adjacent noncancerous tissues from different tumors, this study was the first pan-cancer analysis of PBK/ TOPK and enabled us to observe the expression across all cancers. We only detected lower PBK/TOPK mRNA expression in LAML tissues than in normal tissues, which has not been reported in previous studies, although PBK/TOPK may mediate cell proliferation and viability in promyelocyte cell lines [28].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Although previous studies [1,26,27] have reported higher expression of the PBK/TOPK mRNA and protein in tumor tissues than in adjacent noncancerous tissues from different tumors, this study was the first pan-cancer analysis of PBK/ TOPK and enabled us to observe the expression across all cancers. We only detected lower PBK/TOPK mRNA expression in LAML tissues than in normal tissues, which has not been reported in previous studies, although PBK/TOPK may mediate cell proliferation and viability in promyelocyte cell lines [28].…”
Section: Discussionmentioning
confidence: 90%
“…PDZ binding kinase (PBK) is a kinase that binds to the PDZ2 region of HDIG as first identified by an investigator screening a yeast two-hybrid system [1], and the gene was cloned from a HeLa cell cDNA library. T-LAK cell-derived protein kinase (TOPK) is a serine-threonine protein kinase identified from a cDNA library of activated lymphokineactivated killer T cells [2], and PBK was later identified as the same molecule as TOPK by a sequence analysis, hence receiving the name PBK/TOPK.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the functions of TOPK and its inhibitors have been reviewed in individual studies [ 128 ]; however, no comprehensive or intuitive works have been published, and, thus, a strength of the current paper is that it is more profound and broader than previous reports. In addition, drugs targeting TOPK are not used as frequently as AKT or AURKA drugs in clinical settings [ 129 , 130 ]; however, TOPK is identified here as a novel prognostic predictive factor and is involved in several signaling pathways, such as the MAPK and AKT pathways.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…T-lymphokine-activated killer-cell-originated protein kinase (TOPK), also known as PDZ-binding kinase (PBK), is a novel mitotic serine/threonine protein kinase, which was con rmed to be associated with the development, progression, and metastasis of malignancies and to be a potential therapeutic target in cancer therapy [37]. Studies have shown that PBK expression is increased in various cancers compared with in normal tissues [38].In this study, we explored the expression of PBK in pan-cancers using oncomine and TIMER databases.…”
Section: Discussionmentioning
confidence: 99%